Linking hunting weaponry to attack strategies in sailfish and striped marlin. Issue 1918 (15th January 2020) - Hansen, M. J.; Krause, S.; Breuker, M.; Kurvers, R. H. J. M.; Dhellemmes, F.; Viblanc, P. E.; Müller, J.; Mahlow, C.; Boswell, K.; Marras, S.; Domenici, P.; Wilson, A. D. M.; et al.
Abstract : Linking morphological differences in foraging adaptations to prey choice and feeding strategies has provided major evolutionary insights across taxa. Here, we combine behavioural and morphological approaches to explore and compare the role of the rostrum (bill) and micro-teeth in the feeding behaviour of sailfish ( Istiophorus platypterus ) and striped marlin ( Kajikia audax ) when attacking schooling sardine prey. Behavioural results from high-speed videos showed that sailfish and striped marlin both regularly made rostrum contact with prey but displayed distinct strategies. Marlin used high-speed dashes, breaking schools apart, often contacting prey incidentally or tapping at isolated prey with their rostra; while sailfish used their rostra more frequently and tended to use a slower, less disruptive approach with more horizontal rostral slashes on cohesive prey schools. Capture success per attack was similar between species, but striped marlin had higher capture rates per minute. The rostra of both species are covered with micro-teeth, and micro-CT imaging showed that species did not differ in average micro-tooth length, but sailfish had a higher density of micro-teeth on the dorsal and ventral sides of their rostra and a higher amount of micro-teeth regrowth, suggesting a greater amount of rostrum use is associated with more investment in micro-teeth. Our analysis shows that the rostra of billfish are used in distinct ways and we discuss our results in the broader context of relationships between morphological and behavioural feeding adaptations across species.